Reduction of CO2 emissions using HHO mounted in a car’s motor & its economic - Almassri, Ghassan; Jaballa, Khalid; Maatuga, Benur; Almusbahi, Salah (Sharwes Scientific Journal, 2025)
The HHO cell has been proved itself as most important hybrid fuel, that, it can reduce the fuel consumption and  reduce of the CO2  emission, the objective of this research is reduce of pollution that result from the internal combustion engine that use the gasoline as fuel by using the HHO dry cell. Also using hydrogen cell technology as a way to reduce fuel consumption in vehicles and to reduce harmful emissions to the environment by design hydrogen cell that is inexpensive and with high performance for helping consumers and encourage them to purchase it. Results show that the CO2 emissions in Libya is reduced from 12.24 Mt to 8.39 Mt through driving inside cities and decreasing carbon emissions from 8.55 Mt to 6.53 Mt in combined drive. Also it was reduced fuel consumption for a motor vehicle in the city up to 31.4 %, and 32.9 % between city and combined drive. The benefit of installing HHO cell for all cars in Libya is about 1.26 billion dollar yearly.